Employer branding: Strategic steps to reduce turnover intention - Melanny Methasari; Hepiyanto Hepiyanto (Jurnal Mantik, 2024)
This research aims to examine the influence of employer branding based on its aspects on turnover intention. The population was taken from employees at PT. YMPI Pasuruan at staff level, both permanent employees and contract employees (PKWT) using a quota purposive sampling technique with the Slovin formula with a margin of error of 0.05, obtained 68 employees as sampling. The results of the regression analysis show that the probability value is less than 5% (p<0.05), which shows that all aspects of employer branding, including interest value, social value, economic value, development value and applicant value, have a significant effect on turnover intention. Likewise, partial testing resulted in the results that all aspects of employer branding have a negative and significant effect on turnover intention, which means that the higher the effect of employer branding, as well as the aspects therein, the more it can reduce employee turnover intention. So it can be concluded that interest value, social value, economic value, development value, and applicant value simultaneously or partially have a negative and significant effect on employee turnover intention at PT. YMPI, both permanent employees and contract employees or prospective employees